Predictors of Intrapartum Stillbirths among Women Delivering at Mulago Hospital, Kampala, Uganda - Paul Kiondo; Annettee Nakimuli; Samuel Ononge; Julius Namasake Wandabwa; Milton Wamboko Musaba (Global Health and Education Projects, Inc., 2021)
Background: Over the last decade, Uganda has registered a significant improvement in the utilization of maternity care services. Unfortunately, this has not resulted in a significant and commensurate improvement in the maternal and child health (MCH) indicators. More than half of all the stillbirths (54 per 1,000 deliveries) occur in the peripartum period. Understanding the predictors of preventable stillbirths (SB) will inform the formulation of strategies to reduce this preventable loss of newborns in the intrapartum period. The objective of this study was to determine the predictors of intrapartum stillbirth among women delivering at Mulago National Referral and Teaching Hospital in Central Uganda. Methods: This was an unmatched case-control study conducted at Mulago Hospital from October 29, 2018 to October 30, 2019. A total of 474 women were included in the analysis: 158 as cases with an intrapartum stillbirth and 316 as controls without an intrapartum stillbirth. Bivariable and multivariable logistic regression was done to determine the predictors of intrapartum stillbirth. Results: The predictors of intrapartum stillbirth were history of being referred from lower health units to Mulago hospital (aOR 2.5, 95% CI:1.5-4.5); maternal age 35 years or more (aOR 2.9, 95% CI:1.01-8.4); antepartum hemorrhage (aOR 8.5, 95% CI:2.4-30.7); malpresentation (aOR 6.29; 95% CI:2.39-16.1); prolonged/obstructed labor (aOR 6.2; 95% CI:2.39-16.1); and cesarean delivery (aOR 7.6; 95% CI:3.2-13.7). Conclusion and Global Health Implications: Referral to hospital, maternal age 35 years and above, obstetric complication during labor, and cesarean delivery were predictors of intrapartum stillbirth in women delivering at Mulago hospital. Timely referral and improving access to quality intrapartum obstetric care have the potential to reduce the incidence of intrapartum SB in our community.   Copyright © 2021 Kiondo et al. Published by Global Health and Education Projects, Inc. This is an open-access article distributed under the terms of the Creative Commons Attribution License (CC BY 4.0) which permits unrestricted use, distribution, and reproduction in any medium, provided the original work, first published in this journal, is properly cited.